Smart Sensors for Healthcare and Medical Applications - Formica, Domenico; Schena, Emiliano (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book focuses on new sensing technologies, measurement techniques, and their applications in medicine and healthcare. Specifically, the book briefly describes the potential of smart sensors in the aforementioned applications, collecting 24 articles selected and published in the Special Issue "Smart Sensors for Healthcare and Medical Applications". We proposed this topic, being aware of the pivotal role that smart sensors can play in the improvement of healthcare services in both acute and chronic conditions as well as in prevention for a healthy life and active aging. The articles selected in this book cover a variety of topics related to the design, validation, and application of smart sensors to healthcare.